2017
DOI: 10.4085/1062-6050-52.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Loading During Heel-Raising and -Lowering Exercises

Abstract: Context: Achilles tendinopathies are common injuries during sport participation, although men are more prone to Achilles tendon injuries than women. Heel-raising and -lowering exercises are typically suggested for Achilles tendon rehabilitation.Objective: To compare the estimated Achilles tendon loading variables and the ankle range of motion (ROM) using a musculoskeletal model during commonly performed heelraising and -lowering exercises.Design: Controlled laboratory study. Setting: University biomechanics la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…The subjects were instructed to rise onto their toes as high as possible and followed a rhythm of 1 Hz produced with an electronic metronome. The subjects raised and lowered their heels each for approximately 1 second, which was similar to the previous studies [ 35 , 43 ]. The examination was repeated three times with a rest of 1 minute between two consequent trials, and each trial lasted for about 20~30 seconds.…”
Section: Methodssupporting
confidence: 73%
“…The subjects were instructed to rise onto their toes as high as possible and followed a rhythm of 1 Hz produced with an electronic metronome. The subjects raised and lowered their heels each for approximately 1 second, which was similar to the previous studies [ 35 , 43 ]. The examination was repeated three times with a rest of 1 minute between two consequent trials, and each trial lasted for about 20~30 seconds.…”
Section: Methodssupporting
confidence: 73%
“…57 The strain values obtained (expressed in %) were between 0.71±0.35 and 8.80±0.35, corresponding to the seated heel raising and lowering and the unilateral heel raising and lowering exercises, respectively. 57 Type of exercises Different types of exercises were analysed in the included studies. Heel raising and lowering exercises, involving concentric or eccentric plantarflexion, are commonly applied in Achilles tendinopathy rehabilitation.…”
Section: Open Accessmentioning
confidence: 94%
“…In particular, we found that (1) the distance between the most inferior point of the CB and the most inferior part of the AT insertion into the CB increases with age, (2) the height of the AT insertion into the posterior aspect of the CB decreases with age, and (3) the length of the AT insertion into the posterior aspect of the CB decreases with age. Knowledge of the relationships among the AT's insertion point, age, and pathologies could help in the development of novel strategies for the treatment and prophylaxis of AT injuries specifically tailored to different age groups, and in improving operative techniques and reducing the risk of iatrogenic injuries (Beitzel et al, ; Revak et al, ). This study is a key step toward constructing a computed model that can be used by sports doctors and trainers to increase the awareness of individual differences in the loading anatomy of the AT.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologies of the foot and ankle involving the AT are a common orthopedic problem, mostly encountered among athletes and older adults (Beitzel et al, ; Yilmaz et al, ; Gärdin et al, ; Revak et al, ; Docking et al, ; Risch et al, ; Wengler et al, ). Several factors such as age and sex could account for this heterogeneity in the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation